Nanoparticle Ag-enhanced textured-powder Bi-2212/Ag wire technology. Issue 1 (November 2015) - Kellams, J N; McIntyre, P; Pogue, N; Vandergrifft, J
Abstract: A new approach to the preparation of cores for Bi-2212/Ag wire is being developed. Nanoparticle Ag is homogeneously dispersed in Bi-2212 fine powder, and the mixture is uniaxially compressed to form highly textured, cold-sintered core rods. The rods can be assembled in a silver matrix, drawn to form multifilament wire, and restacked and drawn to form multifilament wire. Preliminary studies using tablet geometry demonstrate that a nonmelt heat treatment produces densification, grain growth, intergrowth among grains, and macroscopic current transport. The status of the development is reported.